It Is Just a Blood Patch: Considerations for Patients with Preexisting Intracranial Hypertension - Devina Shiwlochan; Sargis Ohanyan; Kanishka Rajput (Case Reports in Anesthesiology)
Epidural blood patches are routine procedures interventional pain physicians perform for postdural puncture headaches (PDPH), whether it be due to the inadvertent wet tap from an epidural or a diagnostic lumbar puncture. Typically, these patients are relatively healthy and an epidural is relatively straightforward. However, there are cases complicated by a neurologic history such as benign intracranial hypertension. Here, we present a case of a patient with benign intracranial hypertension (BIH) that suffered a postdural puncture headache after a diagnostic lumbar puncture, with no documented opening pressure, continued on acetazolamide. There have only been a small number of documented cases of BIH complicated by PDPH. We discuss the medical management of BIH, how it can exacerbate a postdural puncture headache, our definitive management with an epidural blood patch, and our concerns of rebound intracranial hypertension. We demonstrate that treatment of PDPH in BIH is best managed with image-guided blood patches, with smaller volume of autologous blood, and at a slower rate.